Generating Long-Read Sequences of Balsa (Ochroma pyramidale (Cav. ex Lam.) Urb.) Using Minion Oxford Nanopore Technology and Utilization for Phylogenetic Study - Siska Nurfajri; Fifi Gus Dwiyanti; Rahadian Pratama; Muhammad Majiidu; Iskandar Z. Siregar (AGRIVITA Journal of Agricultural Science, 2023)
Balsa (Ochroma pyramidale) is fast-growing forest plant species introduced to Indonesia with limited genetic information. Genetic information can be obtained through molecular assessment which is now feasible due to sequencing technology development. This is supported by the third-generation sequencer technology, which has been developed using long-read sequencing technology. MinION Oxford Nanopore Technology is one of the long-read sequence-based sequencers with a real-time process and portable. This study aims to generate genomic data and analyze the phylogenetic relationship of balsa (O. pyramidale) based on long-read sequences with MinION Oxford Nanopore Technologies. Balsa long-read sequencing generated a partial chloroplast genome (cpDNA) sequence of 155,430 bp, which can be used for further DNA barcode-based phylogenetic analysis from the chloroplast genome. Phylogenetic analysis showed that the balsa species (O. pyramidale) was genetically grouped in one clade with other O. pyramidale species in phylogeny analysis based on rbcL, matK, and a combination of rbcL and matK genes indicated that those genes were a suitable marker for phylogenetic analysis in balsa species (O. pyramidale).